Three Novel ACE Inhibitory Peptides Isolated From Ginkgo biloba Seeds: Purification, Inhibitory Kinetic and Mechanism - Ma, Fei-Fei; Wang, Hao; Wei, Chao-Kun; Thakur, Kiran; Wei, Zhao-Jun; Jiang, Li (Frontiers in Pharmacology, 2019)
Alcalase, dispase, trypsin, and flavourzyme were used to hydrolyze the extracted Ginkgo biloba seeds protein isolate (GPI). The Ginkgo protein hydrolysates (GPHs) with the maximum degree of hydrolysis (DH) and ACE inhibitory activity were selected, and ultra-filtered to obtain components with different molecular weights (MW) (<1 kDa, 1-3 kDa, 3-5 kDa, 5-10 kDa). The components with MW of <1kDa showed better ACE inhibition (IC50:0.2227 mg/mL). Purification and identification by Sephadex G-15 gel chromatography and LC-MS/MS conferred three new potential ACE inhibitory peptides [TNLDWY (non-competitive suppression mode), IC50: 1.932 mM; RADFY (competitive inhibition modes), IC50:1.35 mM; RVFDGAV (competitive inhibition modes), IC50:1.006 mM]. Molecular docking depicting the inhibitory mechanism for ACE inhibitory peptides indicated that the peptides bound well to ACE and interacted with amino acid residues at the ACE active site.